تأثير سياسة الرعاية التمريضية على عسرة البلع عند مرضى الجهاز العصبي في وحدات الرعاية المركزة - غزال, سوسن; سلامة, عبد الهادي; الحريري, كامل (Latakia University Journal -Medical Sciences Series, 2017)
تُعد عسرة البلع من أهم المضاعفات الشائعة عند مرضى الجهاز العصبي في وحدات الرعاية المركزة. الهدف: هدفت الدراسة إلى تقييم تأثير سياسة الرعاية التمريضية على عسرة البلع عند مرضى الجهاز العصبي في وحدات الرعاية المركزة. أدوات البحث وطرائقه: أجُريت هذه الدراسة على عينة مؤلفة من (40) مريضاً موزعين على أربعة مجموعات (تمرين ((Shaker، مناورة (Mendelsohn)، تمرين ((Shaker ومناورة (Mendelsohn)، المجموعة الضابطة) في قسم الرعاية المركزة في مستشفى الأسد الجامعي والمستشفى الوطني ممن يعانون من عسرة بلع، جُمعت البيانات باستخدام استمارة تتضمن البيانات الشخصية واستمارة تتضمن مقياس شدة عسرة البلع. النتائج: خلُصت النتائج إلى أن تطبيق تمرين ((Shaker ومناورة (Mendelsohn) مع بعض كان له الأثر الأكبر على إنقاص شدة عسرة البلع، وأوصت الدراسة بضرورة تطبيق تمرين ((Shaker ومناورة (Mendelsohn)، عند المرضى الذين لديهم عسرة بلع.Dysphagia considers the most important and common in neurological system patient on critical care units. Objective: The aim of this study was to study the effect of nursing care policy on dysphagia in neurological system patients in critical care units. Material and method: the study was conducted on 40 patients divided on four groups (Shaker Exercise, Mendelsohn maneuver, [Shaker Exercise, and Mendelsohn maneuver] and control group) in critical care units in the Assad university hospital and the National Hospital whom have dysphagia. The data was collected by using the personal information form, and the dysphagia severity scale. Results: This study showed that Shaker Exercise, and Mendelsohn maneuver together were the most effective in reduce dysphagia levels and recommended about importance of Shaker Exercise, and Mendelsohn maneuver for patients with dysphagia.